Perspektif Mahasiswa Program Studi Pendidikan Bahasa Arab Fakultas Bahasa dan Sastra Universitas Negeri Makassar Terhadap Media Pembelajaran Pada Mata Kuliah Keterampilan Menulis - Sarah Noviyanti L.; Susiawati Susiawati (Seminar Nasional LP2M UNM, 2019)
The purpose of this study was to determine the students' perspectives on learning media and find out what learning media were the most desirable for students of the Arabic Language Education Study Program at FBS UNM in the writing Imla’ subject. This research is a descriptive qualitative research. The research subjects in this study were students of the Arabic Language Education Study Program Faculty of Language and Literature at Makassar State University who had passed the Imla’ I and II subjects. The sample used was purposive sampling and snowball sampling. Data analysis techniques in this study used data analysis techniques by Miles and Huberman models. From the results of the questionnaire found 62 (78.5%) students chose Powerpoint media as the most popular media. And found 12 (15.2%) students chose the library media as a medium for learning Imla’ subjects. And found 11 (13.9%) students who liked social media LINE and WhatsApp for learning Imla’ subjects. Only 5 (6.4%) students liked photo and picture media. While from the interviews of 21 students, it was found that 15 students chose Powerpoint media as the most popular media, 5 students chose social media LINE and WhatsApp as the most interesting media, and only 1 student chose photo and picture media as the preferred media in Imla’ learning